Pengembangan Sistem Informasi Berbasis Web dengan Menggunakan Metode Agile: Studi Kasus Pengelolaan Proyek TI - Samosir, Khairunnisa; Gusla Nengsih, Yeyi (Jurnal Informatika, Komputer dan Bisnis (JIKOBIS), 2024)
In this study, we developed a web-based information system for Information Technology (IT) project management using the Agile approach. This system aims to improve efficiency and effectiveness in project management by providing various features, such as project progress monitoring, resource management, and communication between team members. In developing the system, needs analysis, design, implementation, and testing were carried out using the Agile method which focuses on collaboration and adaptation to change. The results of this study indicate that the use of the Agile method in developing web-based information systems can improve flexibility and responsiveness to changes in user needs.